The Gender’s Perception on Pre-Service Teacher’s Anxiety in Teaching English - Nina Hayuningtyas; Mega Fariziah Nur Humairoh; Nidom Hamami; Siti Khodijah (LP2M UIN Kiai Haji Achmad Siddiq Jember, 2022)
Teaching practice gives students experience and opportunities to learn how to teach in real schools. However, some may feel anxiety because they lack of teaching experience. Male and female could have different feelings. This feeling can cause potential problems to their learning and teaching process. This research aimed to discover the gender’s perception caused of Indonesian pre-service teachers’ anxiety in teaching English. This research employed both quantitative and qualitative methods. The data were collected from questionnaires and interview. The results show that several perceptions based on their gender contributing to pre-service teachers’ anxiety, namely: confidence, English teaching skills, preparation, lesson delivery, students’ profiles, evaluation skill and class management. While, in solving the problems, the participants applied personal, professional, social, and institutional coping strategies. Knowing the factors contributing the students’ anxiety in speaking based on the gender and how to solve it gave the pre-service teacher opportunity to reduce them